Infection, Immunodeficiency, and Inflammatory Diseases in Autoimmune Neurology - Piquet, Amanda L.; Clardy, Stacey L. (Seminars in Neurology, 2018)
When patients present with neurological syndromes, such as encephalopathy/encephalitis, meningitis, and/or myelopathy/myelitis, the differential diagnosis is often broad, including infectious, inflammatory, autoimmune, vascular, and neoplastic etiologies. Just with inflammatory and autoimmune etiologies alone, there are numerous causative diseases. A comprehensive history and physical examination investigating for extraneurologic manifestations of immune-mediated disease is often necessary. Moreover, evaluating for an underlying infection and/or immunodeficiency becomes a critical aspect to the workup. This article will focus on the association of viral infections and dysregulation of the immune system as triggers of autoimmunity, in addition to various systemic inflammatory diseases that can cause neurological disease either with or without an established rheumatological disorder.
Keywords: autoimmunity; common variable immunodeficiency disease; sarcoidosis; systemic lupus erythematous; Sjögren's syndrome; inflammatory disorder